Bibliometric Mapping of Publications on Digital Transformation and Adaptation of Sharia-Based Household Economics in Indonesia - Erizal Candra Efendi; Indah Permata Sari; Fitriani Fitriani; Hafni Juniyanti Hsb (INCOME: Innovation of Economics and Management, 2026)
The development of digital technology has reshaped patterns of economic activity, including scholarly discussions on Muslim household economics in Indonesia. This study aims to map and describe the research landscape on digital transformation and the adaptation of Sharia-based household economics in Indonesia by examining publication trends, collaboration structures, and thematic orientations. Using a bibliometric approach, data were retrieved from Scopus, Dimensions, Garuda, and Google Scholar, covering the period 2013–2024. After screening and deduplication, publications were included in the analysis. Bibliometric mapping and performance analysis were conducted using VOSviewer and Biblioshiny. The results indicate a steady increase in publications from 2016, with a peak in 2023. Co-authorship analysis reveals growing research collaboration, characterized by increasingly interconnected and multidisciplinary author networks. Co-word and thematic analyses identify digital economy, Islamic finance, and Sharia-based household economics as dominant and interrelated themes, reflecting the main directions of scholarly attention in this field. Citation and keyword network structures suggest that research has increasingly focused on the intersection of digital innovation and Islamic economic principles. Overall, this study maps the evolution and structure of the literature on digital transformation and Sharia-based household economics in Indonesia. The findings provide a systematic overview of research trends and collaboration patterns, offering a reference point for future empirical, theoretical, and policy-oriented studies in digital Islamic economics.